Pengaruh Tim Swakelola dan Kepuasan Kerja terhadap Produktivitas Guru SD di Kecamatan Cikedal Banten - Ina Ayu Agustina (SAP (Susunan Artikel Pendidikan), 2018)
Managing a team independently or called as a self-managed team and job satisfaction are factorsimportant for an institution to achieve its goal, such as to improve and produce quality human resource performance. The purpose of this study is to examine and analyze the effect of self-managed team on teacher’s productivity, the effect of job satisfaction on teacher’s productivity and the effect of self-managed team on job satisfaction. The population of this research is Elementary School (SD) teachers at SD Cikedal Banten. The reachable population of this study is the teachers belonging to clusters IV and V. The sample of this study is 96 people taken using a simple random technique. The method used in this research is survey method, in which the data are collectedby distributing questionnaires. The data are then analyzed using path analysis. The result of the research shows that (1) self-managed team has a positive and significant effect on teacher’s productivity, (2) job satisfaction has a positive and significant effect on teacher’s productivity and (3) self-managed team has a positive and significant effect on job satisfaction.